ADVOKASI KORBAN KEKERASAN SEKSUAL DALAM PERSPEKTIF KOMUNIKASI ISLAM: STUDI KASUS DI UPTD PPA PROVINSI KALIMANTAN TIMUR - Tindas Gustiana, Mona; Wijaya, Ida Suryani (HIKMAH : Jurnal Dakwah Dan Sosial, 2026)
Abstract. The surge in sexual violence cases in East Kalimantan Province (579 cases as of September 2022) demands an advocacy model that goes beyond formal legal approaches. This study analyzes victim advocacy through an Islamic communication perspective at the UPTD PPA (Principal Implementation Unit for Women and Children), using a qualitative case study approach on five cases (2022–2023). Data were collected through interviews, observation, and documentation, and analyzed thematically. The results indicate that the advocacy standard operating procedure (SOP) effectively integrates legal, psychological, and medical services, and is reinforced by the Islamic communication ethics of qaulan ma'rufan (good character), ta'awun (conciliation), and da'wah bil hal (prosperous character) and bil qaul (prosperous character). This integration accelerates the restoration of victims' dignity, reduces re-victimization, and builds collective empathy. Advocacy serves as an instrument of social transformation through shura (law and order) and maqasid (objectives of sharia). These findings confirm that advocate Islamic communication is a strategic operational framework that strengthens the fulfillment of victims' rights while accelerating the welfare of the ummah. Abstrak. Lonjakan kasus kekerasan seksual di Provinsi Kalimantan Timur (579 kasus hingga September 2022) menuntut model advokasi yang melampaui pendekatan legal formal. Penelitian ini menganalisis advokasi korban melalui perspektif komunikasi Islam di UPTD PPA dengan pendekatan kualitatif studi kasus terhadap lima kasus (2022–2023). Data dikumpulkan melalui wawancara, observasi, dan dokumentasi, serta dianalisis secara tematik. Hasil menunjukkan bahwa SOP advokasi efektif mengintegrasikan layanan hukum, psikologis, dan medis, serta diperkuat oleh etika komunikasi Islam qaulan ma’rufan, ta’awun, dan dakwah bil hal serta bil qaul. Integrasi ini mempercepat pemulihan martabat korban, menekan reviktimisasi, dan membangun empati kolektif. Advokasi berfungsi sebagai instrumen transformasi sosial melalui syura dan maqasid syariah. Temuan ini menegaskan komunikasi Islam advokatif sebagai kerangka operasional strategis yang memperkuat pemenuhan hak korban sekaligus mengakselerasi maslahah ummah.